E-commerce quality and evaluation framework based on technical and user perspectives - Abd Wahab, Alawiyah; Ahmad, Faudziah; Baharom, Fauziah; Yahaya, Jamaiah (Universiti Utara Malaysia, 2014)
The study produces an e-commerce quality and evaluation (ECQE) framework based on consumer perspectives.It was conducted in four main phases that include: 1) theoretical study; 2) empirical study; 3) e-commerce quality and evaluation framework construction and development, and 4) confirmation study. The ECQE framework includes four components: quality factors that deal with user expectation and satisfaction; assessment entity, assessment specification, and quality level.The framework was tested on six e-commerce websites.Results show that the ECQE framework is applicable and realistic.The ECQE framework offers a guidance and standard procedure for e-commerce website quality evaluation that can be used to improve organization websites to meet the consumers need and to keep the organization competitive and sustainable.